International Conference on Precision Health in the Industrial Revolution 4.0 (IC-PHIR) 26-27th August 2023 / Faculty of Medicine, UiTM - UiTM, Faculty of Medicine (Faculty of Medicine, 2024)
Journal of Clinical and Health Sciences, Vol 9 Issue 1 (Supplementary) 2024